The Prospective Urban Rural Epidemiology (PURE) study: PURE Turkey - ÇALIK, KEVSER BURCU (TURKISH SOC CARDIOLOGY, 2018)
Objective: The Prospective Urban Rural Epidemiology (PURE) study is a prospective cohort study that collects data on social, environmental, and individual risk factors and chronic diseases among residents of 25 countries in the range of 35 to 70 years of age, living in rural and urban areas. The PURE study is directed by the Population Health Research Institute of McMaster University in Canada. In Turkey, the study is conducted by the Metabolic Syndrome Society. Methods: In Turkey, the study is being conducted in 8 cities. The initial fieldwork began in 2008. Questionnaires were completed, and anthropometric measurements, blood and urine samples, handgrip strength evaluations, electrocardiogram readings, and spirometer and body composition measurements were obtained. Each year, participants were followed up via telephone. Every third year, questionnaires, field measurements, and biological data sampling were repeated. Results: PURE Turkey has 4056 participants (female: 60.7%, male: 39.3%; mean age: 50 +/- 9.1 years). Among them, 43.9% had metabolic syndrome and 52.8% were obese. The prevalence of hypertension was 41.1% and proportion of controlled hypertension was 34%. A total of 2098 (51.7%) of the participants had a total cholesterol of >= 200 mg/dL or were using a lipid lowering agent. In patients with diabetes, 79.8% had low-density lipoprotein cholesterol levels >= 100 mg/dL. Although a dramatic change was not observed in those parameters in the follow-up years, the prevalence of diabetes mellitus increased from 13.7% in 2008 to 21% in 2015. The baseline and follow-up data of the PURE study were analyzed with the other countries participating in the study and reported for international publication. Conclusion: The PURE study is a large, ongoing, prospective epidemiological study that is investigating the causes of the causes of noncommunicable diseases in the world. In addition to revealing the health status of nations, the study also has the potential to affect health politics.
Keywords: Diabetes; hyperlipidemia; hypertension; Prospective Urban Rural Epidemiology; Turkey; LOW-INCOME COUNTRIES; CARDIOVASCULAR-DISEASE; MIDDLE-INCOME; SECONDARY PREVENTION; POTASSIUM EXCRETION; URINARY SODIUM; BLOOD-PRESSURE; MORTALITY; AFFORDABILITY; AVAILABILITY